NA. Efektivitas Program Penanganan Anak Putus Sekolah di Kota Mataram (Studi Kasus di Dinas Sosial Kota Mataram - Nadia Aprilia (Yayasan Masyarakat Cita Insani (YAMACITA): Bergerak Dibidang Penelitian, Pendidikan, Pelatihan, Reasearch, 2025)
Abstract: The problem in this research aims to evaluate the effectiveness of the program for handling school dropouts in Mataram City, with a case study at the Mataram City Social Service. The school dropout handling program in Mataram City can serve as an example for other cities in improving educational access for school dropouts. Until now, Indonesia is still facing issues with children. This type of research is evaluative research. The evaluation method used in this study is the coaching model evaluation. Therefore, the researcher conducted an analysis of the assumptions/perceptions of the community. The researcher conducted an analysis of the assumptions/perceptions of the community. The results of the research conducted by the researcher at the Social Services of Mataram City in services covering the components of Reaction, Learning, Behavior, and Result (Kirkpatrick) show that the results obtained from the Reaction component had a percentage of 116.39%, the Learning component had 112.56%, the Behavior component during the service amounted to 113%, and the final result of the Result component was 100.375%. Of the four components above, the average is 90%. Therefore, the conclusion of the research on the Effectiveness of the Program for Handling Dropout Children at the Social Services of Mataram City (Case Study at the Social Services of Mataram City) is that overall it falls into the very effective category. Abstrak: Permasalahan dalam penelitian ini adalah bertujuan untuk mengevaluasi efektivitas program penanganan anak putus sekolah di Kota Mataram, dengan studi kasus di Dinas Sosial Kota Mataram. Program penanganan anak putus sekolah di Kota Mataram dapat dijadikan contoh bagi kota-kota lain dalam meningkatkan akses pendidikan bagi anak-anak putus sekolah. Sampai saat ini bangsa Indonesia masih diperhadapkan dengan masalah anak-anak. Jenis penelitian ini adalah penelitian evaluatif. Adapun metode evaluasi yang digunakan dalam penelitian ini adalah evaluasi model pembinaan. Maka peneliti melaksanakan analisis terhadap asumsi/persepsi masyarakat. Hasil penelitian yang peneliti lakukan di Dinas Sosial Kota Mataram dalam pelayanan yang meliputi komponen Reaction, Learning, Behavior dan Result (Kirkpatrick) maka dari itu hasil yang diproleh dari komponen Reaction dengan jumlah prosentase sebesar 116,39%, komponen Learning sebesar 112,56%, komponen Behavior selama pelayanan dengan jumlah sebesar 113%, dan hasil akhir komponen Result dengan jumlah 100,375%, dari 4 komponen diatas memiliki rata-rata sebesar 90%. Maka dari itu kesimpulan dari hasil penelitian Efektivitas Program Penanagan Anak Putus Sekolah di Dinas Sosial Kota Mataram (Studi Kasus di Dinas Sosial Kota Mataram). Secara keseluruhan masuk dalam kategori sangat efektif.